The Optimization of Flow Shop Scheduling in Milling Stoper Production Using Campbell Dudek Smith Algorithm - Haposan Vincentius Manalu; Insan Kamil; Oki Setiawan; Darti Purnama Sari; Siti Adriani; Ifti Luthviana Dewi; Robi Kurniawan; Lavita Indriani Br. Ginting; Khollilah Nuraini (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2026)
Non-optimal production scheduling in a flow shop system can increase makespan, idle time, and workload imbalance among machines. This study aims to optimize the production scheduling of a milling stopper in a manufacturing workshop using the CDS algorithm. This research contributes to improving the efficiency of production systems, particularly in conventional machining processes. The data used consist of processing times for four jobs. The CDS algorithm generates six alternative scheduling sequences, which are then compared based on their makespan values. The results show that the best job sequence is obtained in the fourth iteration, with the order starting from Top Arm, Bottom Arm, Base, and Silinder, resulting in a makespan of 1599 minutes. The Gantt chart indicates that the bottleneck occurs at the conventional milling machine, while idle time arises due to imbalanced processing times among machines. This study demonstrates that the CDS algorithm is effective in minimizing makespan and improving the efficiency of flow shop production systems.